Endoscopic Lumbar Surgery: The State of the Art in 2019 - Alexander J. Butler; Milad Alam; Kevin Wiley; Alexander Ghasem; Augustus J. Rush III; Jeffrey C. Wang (Neurospine, 2019)
This study was aimed to provide a brief historical perspective to facilitate appreciation of current techniques, describe outcomes of endoscopic lumbar surgery relative to those of existing techniques, and identify topics in need of study and future directions for the field of endoscopic lumbar surgery. Using the PubMed database, a comprehensive search was conducted to identify peer-reviewed English language articles pertaining to endoscopic lumbar surgery. Lack of focus on pertinent techniques or lack of outcome measures constituted exclusion criteria. A majority of included articles were published from 2015–2019. A context with which to appreciate the application of endoscopic lumbar techniques is established. An abundance of case series and several recent comparison studies have documented the benefits and potential pitfalls of these methods in the past two decades. The advantages of endoscopic lumbar spine surgery are widely touted to include reduced perioperative morbidity, including blood loss, operative time and immediate postoperative recovery, minimal structural trauma resulting from surgery, generally positive patient report outcome scores and the potential to contain costs. Additional high-quality research assessing outcomes of endoscopic lumbar surgery are certainly needed and currently expected given the rapid expansion of the field in recent years.